Double Modification of Polymer End Groups through Thiolactone Chemistry. Issue 12 (4th May 2016) - Driessen, Frank; Martens, Steven; Meyer, Bernhard De; Du Prez, Filip E.; Espeel, Pieter
Abstract : A straightforward synthetic procedure for the double modification and polymer–polymer conjugation of telechelic polymers is performed through amine‐thiol‐ene conjugation. Thiolactone end‐functionalized polymers are prepared via two different methods, through controlled radical polymerization of a thiolactone‐containing initiator, or by modification of available end‐functionalized polymers. Next, these different linear polymers are treated with a variety of amine/acrylate‐combinations in a one‐pot procedure, creating a library of tailored end‐functionalized polymers. End group conversions are monitored via SEC, NMR, and MALDI‐TOF analysis, confirming the quantitative modification after each step. Finally, this strategy is applied for the synthesis of block copolymers via polymer–polymer conjugation and the successful outcome is analyzed via LCxSEC measurements. Abstract : Double modification of polymeric end groups is performed by synthesizing thiolactone end‐functionalized polymers. In this way, two distinguished functionalities have been introduced in a one‐pot procedure on the same reactive handle, resulting in a library of telechelic structures. Furthermore, this strategy has been applied for polymer–polymer conjugation.